On the Antibiotic and Antifungal Activity of Pestalone, Pestalachloride A, and Structurally Related Compounds - Augner, Daniel (2013)
Pestalone (1) is a prominent marine natural product first isolated by M. Cueto et al. in 2001 from a cofermentation of a marine fungus with a marine bacterium. For more than 10 years, 1 had been considered as a promising new antibiotic compound, the reported MIC against methicillinresistant Staphylococcus aureus (MRSA) being 37 ng/mL. After overcoming the limited availability of 1 by total synthesis (N. Slavov et al., 2010) we performed new biological tests, which did not confirm the expected degree of antibiotic activity. The observed activity of pestalone against different MRSA strains was 3−10 μg/mL, as determined independently in two laboratories. A number of synthetic derivatives of 1 including pestalachloride A and other isoindolinones (formed from 1 by reaction with amines) did not exhibit higher activities as compared to 1 against MRSA and a series of plant pathogens.